PERLINDUNGAN HUKUM TERHADAP HAK ANAK PELAKU TINDAK PIDANA PEMERKOSAAN DALAM SISTEM PERADILAN PIDANA - Meily, Meily (Katalogis, 2017)
The research was to identify and analyze the satisfaction of rights of underage rapists in criminal justice system and legal protection to the rights of underage rapists in criminal justice system. It was a juridical and normative research adopting legal and conceptual approaches. The legal materials and sources referred to primary laws and secondary laws. The legal materials were collected through library studies. The legal materials were analyzed descriptively and concluded deductively. Referring to the results of the analysis, it generated two conclusions. (1) It was preferable to satisfy the rights of underage rapists by settling the case out of courts to set them free from criminal sanctions. Unfortunately, a punishment that longer than an imprisonment may lead ignorance to their rights. (2) The government failed to give legal protection to the rights of underage rapists as it failed to set them free from punitive sanctions. A punitive sanction is no longer effective punishment. It is preferable to affect upbringing for them.